Nitride layers on uranium surfaces. Issue 3 (August 2018) - Liu, Kezhao; Wang, Xiaofang; Liu, Jing; Hu, Yin; Zhong, Huoping; Pan, Qifa; Luo, Lizhu; Chen, Shouchuang; Zhang, Yongbin; Long, Zhong
Abstract: Uranium as an important energy material plays a significant role within the field of material sciences and nuclear industrial applications. However, metallic uranium is chemically active in ambient environment and is easily oxidized and corroded, leading to not only deterioration of its properties and failure of performance as working components but also nuclear pollution of the environment. Therefore, the development of corrosion protection systems for metallic uranium is an issue of prime importance. In view of the nitridation technology in Ti and Fe-based alloys, the successful application to improve the surface wear hardness and corrosion resistance, several nitridation methods have been developed for the surface modification of metallic uranium. Many studies have shown that the surface nitridation of metallic uranium can efficiently improve its corrosion resistance. The surface oxidation layer thickness is as thin as several nanometers even if placed 4 years in the atmosphere. At the present, nitridation of uranium surface is considered as the most promising surface modification way to protect uranium from corrosion. To design and fabricate nitride layers on uranium surface with reliable long-term protective effects, however, one needs deep understanding on the relationships among the physical and chemical properties of the nitride layers, the composition and structure of the layers, and the dependence on the techniques and the processing parameters. One also needs deep understanding on the corrosion behavior of the prepared nitride layers in the environment, and the related corrosion mechanism. In this review, we bring to the readers the achievements and recent advances on the uranium nitridation in the world, including the processing techniques and the related studies on the formation mechanism of the nitride layers, and the understanding on the property-processing-corrosion performance relationship of the layers, aiming at the development of high-performance resistance layers for metallic uranium by the surface nitridation technique. In the review (1) the surface nitridation techniques developed recently, the relationship between the preparation parameters and the composition as well as the structure of the surface layer are summarized; (2) the fundamental physical properties of the uranium nitrides are summarized, depicted and discussed; (3) the influence of the nitrides structure and composition and of the environment on resistance to corrosion as well as the formation mechanism of corroded products in oxidizing environments are depicted and discussed; (4) the potential application of uranium nitrides in other application field such as the application of thermal-electrical conversion is also discussed. Finally, the prospective on the investigations of nitride layers is suggested.